"Městské legendy" na pomezí oborů: antropologický, folkloristický nebo sociologický diskurs? - Petr Janeček (AntropoWebzin, 2009)
Theoretical approach to contemporary oral narratives such as „urban legends“, rumour or gossip has been always afflicted by artifical gaps between various academical fields, most notably between social sciences (social anthropology, sociology) and humanities (folkloristics, literary science). Presented article briefly sumarizes some of the most interesting main theories - but also defficiences - of contemporary folklore studies in fields of folkloristics, literary theory, social antropology and sociology, and calls for multidisciplinary analysis of this phenomenon.